Automatic Detection of Optic Disc and Its Center in Color Retinal Images: A Review - IS, Rajesh; A, Bharathi Malakreddy; C, Maithri; Krishnamurthy, Manjunath Sargur; MS, Shashidhara (International Journal of Computer Sciences and Engineering, 2024)
Optic Disc (OD) is the most critical component of the human retina where blood vessels originate. In the normal retinal image OD appears as a round, bright yellowish region. An efficient localization of OD in color retinal fundus images is the most vital phase for the retinal image analysis and this information helps in finding severity of retinal diseases. Identification of OD accurately is a very difficult and challenging task because of various reasons, including the presence of lesions around the OD and variation in size, shape and color of the optic disc. In this review paper, a brief introduction about OD and some important properties of it are described. A literature survey on OD detection and the complications involved in OD detection are also discussed in this paper.